2021
DOI: 10.1177/19714009211017787
|View full text |Cite
|
Sign up to set email alerts
|

Detection of multiple sclerosis lesions in the cervical cord: which of the MAGNIMS ‘mandatory’ non-gadolinium enhanced sagittal sequences is optimal at 3T?

Abstract: Background and purpose The magnetic resonance imaging in multiple sclerosis consensus guidelines currently mandate three sagittal non-contrast enhanced sequences of T2-weighted fast spin echo, proton density-weighted fast spin echo and short tau inversion recovery; however, these particular three sequences have not previously been compared at 3T. This study compared T2-weighted fast spin echo, proton density-weighted fast spin echo, short tau inversion recovery as well as the double inversion recovery sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In the study of spinal cord MS lesions, DIR is not commonly included in MR protocols, 40–42 even though the current guidelines 28 underline the importance of spinal cord examination at disease onset and during monitoring. While, on the one hand, it has been shown that DIR allows better detection of lesions of the cervical segment in comparison with conventional turbo spin echo sequences, 43 on the other hand, proton density‐weighted fast spin echo and short tau inversion recovery can detect more lesions compared to DIR 44 . Our results, despite being obtained only in the cervical segment of the spine, demonstrated a clearly better detection of MS lesions by using T2P, which encourages further studies to assess whether T2PDIR, either with or without ID, may be considered for future inclusion in MRI protocols addressing spinal cord lesions in MS.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of spinal cord MS lesions, DIR is not commonly included in MR protocols, 40–42 even though the current guidelines 28 underline the importance of spinal cord examination at disease onset and during monitoring. While, on the one hand, it has been shown that DIR allows better detection of lesions of the cervical segment in comparison with conventional turbo spin echo sequences, 43 on the other hand, proton density‐weighted fast spin echo and short tau inversion recovery can detect more lesions compared to DIR 44 . Our results, despite being obtained only in the cervical segment of the spine, demonstrated a clearly better detection of MS lesions by using T2P, which encourages further studies to assess whether T2PDIR, either with or without ID, may be considered for future inclusion in MRI protocols addressing spinal cord lesions in MS.…”
Section: Discussionmentioning
confidence: 99%
“…The current criteria from the MAGNIMS network recommends the use of sagittal noncontrast T2, proton density, and short tau inversion recovery (STIR) for the evaluation of MS lesions in the spinal cord. 7 Despite this, spinal cord evaluation has remained a challenge due to multiple factors, including the small size of the cord and artifacts caused by movements such as respiration, swallowing, and cardiac pulsations. 8 Double inversion recovery (DIR) is a MRI sequence wherein signal from the cerebrospinal fluid is suppressed (as with FLAIR).…”
Section: Introductionmentioning
confidence: 99%
“…DIR has been shown to be sensitive and specific, particularly in evaluation of cerebral cortical/juxtacortical demyelinating lesions 11 . However, based on current studies, there has been mixed data with studies supporting either superiority or inferiority of DIR in detecting demyelinating lesions in the cervical cord, with recent studies available having limited sample size 7,8,11 . The aim of the study was to explore the possibility of using volumetric DIR from brain MRI to study MS lesions of the upper cervical cord.…”
Section: Introductionmentioning
confidence: 99%